Perception, Farm – Level Management and Production Constraints of Fall Army Worm (Spodoptera frugiperda) Among Maize Farmers in Imo State, Nigeria - J.U., Chikaire; M.N., Ibeh; G.O., Aminu; J.C., Oparaojiaku; C.O., Osuagwu; P.A., Onoh; C.C., Godson–Ibeji; J.O., Ajaero (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
One of the major threats to maize farming in Africa, especially Nigeria, is the menace of fall army worm. It has attacked to the point of reducing both quantity and quality leasing to eventual death of plant. Therefore, fall armyworm (FAW) being a serious menace to maize, a staple grain in Nigeria, need be controlled. This paper investigates maize farmer’s perception of the fall armyworm (FAW), menace; the farm- level management practices and production constraints. Using questionnaire, 450 maize farmers purposively selected among maize farmers were interviewed. Mean (M) and percentages were used in analyzing data. Results showed that, farmers already knows the serious of fall army-worm infestation. They agreed that army-worms does great damage to the maize plant (M=42), reduces maize quality (M=2.89), great threat to maize production (M=3.50%), among others. To manage it, chemical insecticides /pesticides are used (99.3%), practice of crop rotation (100%), use of other crops as trap (95.5%), manual collection, distract of eggs/larvae (90.4%), early planting of maize (91.7%) and other measures. However, farmers face the following problems of producing maize under fall armyworm attack; high cost of pesticides (100%), high cost of labour charges (93.5%), inability to identity fall army-worm early (95.7%), unable to use the right amount of chemical (89.1%), lack of training on chemical use (96%), among other challenges.